2021
DOI: 10.1111/raq.12536
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary review ofTetradesmus obliquus: a microalga suitable for large‐scale biomass production and emerging environmental applications

Abstract: Microalgae biomass is among one of the most promising sustainable raw materials for many industrial sectors especially biodiesel production. Although a great diversity of microalgae species has been described and isolated, few have been used for large-scale cultivation. This review presents a multidisciplinary overview of studies on Tetradesmus obliquusa freshwater microalga suitable for largescale production and emerging environmental applications. It reviews the taxonomic history of T. obliquus and its poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 179 publications
(294 reference statements)
2
43
0
Order By: Relevance
“…This ω-3 is an essential FA of the greatest importance for humans and mammals, and can be metabolized into another longer ω-3 PUFA, such as eicosapentaenoic acid (EPA, C20:5 ω-3) and docosahexaenoic acid (DHA, C22:6 ω-3) [ 4 ]. These results are in line with what was previously reported for S. obliquus ; however, some studies have reported high abundances of EPA in this microorganism, which we do not report [ 69 , 70 , 71 , 72 ]. Nonetheless, variations in cultivation might justify the absence of EPA, as salinity, nitrogen, and nutrient stress affect the composition and yield of FA [ 73 , 74 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This ω-3 is an essential FA of the greatest importance for humans and mammals, and can be metabolized into another longer ω-3 PUFA, such as eicosapentaenoic acid (EPA, C20:5 ω-3) and docosahexaenoic acid (DHA, C22:6 ω-3) [ 4 ]. These results are in line with what was previously reported for S. obliquus ; however, some studies have reported high abundances of EPA in this microorganism, which we do not report [ 69 , 70 , 71 , 72 ]. Nonetheless, variations in cultivation might justify the absence of EPA, as salinity, nitrogen, and nutrient stress affect the composition and yield of FA [ 73 , 74 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, variations in cultivation might justify the absence of EPA, as salinity, nitrogen, and nutrient stress affect the composition and yield of FA [ 73 , 74 , 75 , 76 ]. Additionally, the way S. obliquus biomass is processed has been shown to affect the abundance of FA [ 69 ]. The high abundance of this essential FA in S. obliquus contributes to the valorization of this microalga as a source of this essential ω-3 FA as a food ingredient.…”
Section: Discussionmentioning
confidence: 99%
“…To face photoinhibition, algae have developed protection systems based on carotenoids, phenols and other antioxidant biomolecules to prevent the accumulation of free radicals and species reactive to oxygen. T. obliquus contains different bioactive molecules such as pigments (carotenoids and chlorophylls), phenols, proteins, polysaccharides and fatty acids [ 74 ]. These biomolecules give to T. obliquus antioxidant and antiviral properties [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…A growing attention to functional food has driven research into the physiological effects of high biological value components [ 12 ]. Microalgae are among the most promising sources of bioactive compounds for new food products, which can be used to enhance the nutritional value of foods due to their well-balanced chemical composition and their potential anticancer, anti-diabetes, anti-inflammatory and antioxidant properties [ 13 , 14 ]. The addition of microalgae biomass to food products has become an interesting method for providing nutritional supplementation with biologically active compounds, like fatty acids, essential amino acids, polysaccharides, vitamins, carotenoids, and others [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%